The destruction of mucosal barriers, epithelial remodeling, and impaired mucociliary clearance: possible pathogenic mechanisms of Pseudomonas aeruginosa and Staphylococcus aureus in chronic rhinosinusitis - Zahra Chegini; Milad Noei; Jaber Hemmati; Mohammad Reza Arabestani; Aref Shariati (2023)
Abstract Chronic rhinosinusitis (CRS) is a pathological condition characterized by persistent inflammation in the upper respiratory tract and paranasal sinuses. The epithelium serves as the first line of defense against potential threats and protects the nasal mucosa. The fundamental mechanical barrier is formed by the cell-cell contact and mucociliary clearance (MCC) systems. The physical-mechanical barrier is comprised of many cellular structures, including adhesion junctions and tight junctions (TJs). To this end, different factors, such as the dysfunction of MCC, destruction of epithelial barriers, and tissue remodeling, are related to the onset and development of CRS. Recently published studies reported the critical role of different microorganisms, such as Staphylococcus aureus and Pseudomonas aeruginosa , in the induction of the mentioned factors. Bacteria could result in diminished ciliary stimulation capacity, and enhance the chance of CRS by reducing basal ciliary beat frequency. Additionally, bacterial exoproteins have been demonstrated to disrupt the epithelial barrier and induce downregulation of transmembrane proteins such as occludin, claudin, and tricellulin. Moreover, bacteria exert an influence on TJ proteins, leading to an increase in the permeability of polarized epithelial cells. Noteworthy, it is evident that the activation of TLR2 by staphylococcal enterotoxin can potentially undermine the structural integrity of TJs and the epithelial barrier through the induction of pro-inflammatory cytokines. The purpose of this article is an attempt to investigate the possible role of the most important microorganisms associated with CRS and their pathogenic mechanisms against mucosal surfaces and epithelial barriers in the paranasal sinuses.